A rare cause of maternal and fetal mortality by rupture of splenic artery aneurysm – a case report (Journal of Forensic Medicine & Toxicology, 2025)
A 26 year old pregnant female was brought unresponsive to the hospital with alleged history of loss of consciousness fol lowing giddiness. On examination, pulse was not palpable and blood pressure was not recordable. Inspite of all the resus citative measures, she could not be revived. Fetal bradycardia was detected with doppler and emergency perimortem  Caesarean Section was done. But the fetus was still born. At the autopsy of the mother, spleen was found to be enlarged  with multiple areas of hemorrhage. The splenic artery was seen to be tortuous and showed an area of aneurysmal dilata tion and rupture, 3cm proximal to hilum with surrounding peri-pancreatic hematoma. Peritoneal cavity contained one  litre of fluid blood with blood clots in the lesser sac. Histopathological examination revealed arterio-venous malforma tion in the spleen with large areas of haemorrhage. Splenic artery aneurysm is a rare clinical entity that carries the risk of  rupture and fatal hemorrhage. Ruptured splenic artery aneurysm can be disastrous for both the mother and fetus
Keywords: Splenic artery aneurysm; Aneurysmal rupture; Visceral artery aneurysm; Maternal mortality; Fetal mortality